The Role of Stakeholders in Strengthening Communication Networks to Foster Farmers’ Economic Institutions - Anggreany, Shinta; Sumardjo , Sumardjo; Lubis, Djuara P; Syahyuti, Syahyuti (Politeknik Pembangunan Pertanian Bogor, 2025)
The growing number of smallholder farmers in Indonesia necessitates the strengthening of economic institutions through the farmer corporation model. This study examines the role of stakeholders in strengthening communication networks to support farmer institutions in Jayakerta District, Karawang. Using a mixed-methods approach, data were collected from 281 farmers through surveys and 28 stakeholders through in-depth interviews. The results show that coordination among stakeholders remains limited. Communication network analysis reveals that farmers with high centrality are more actively involved in exchanging production-related information, while those with low centrality tend to seek marketing information but have limited interaction. Spearman’s test indicates that internal farmer factors do not significantly influence communication networks (ρ = 0.072; p > 0.05), whereas stakeholder support shows a negative yet significant correlation (ρ = -0.128; p < 0.05), indicating a mismatch between the form of support provided and the farmers’ actual needs. Although support is provided in various forms, its integration is not yet optimal. Strengthening communication networks and ensuring consistent stakeholder involvement are key to the success of farmer corporations. Local actors, such as voluntary agricultural extension agents, play a crucial role in reinforcing farmer information exchange. The low level of digital literacy among farmers also calls for policy interventions through training and capacity-building programs. These findings underscore the importance of integrated communication systems in supporting institution-based agricultural development in Indonesia.